2013
DOI: 10.1080/09640568.2013.839442
|View full text |Cite
|
Sign up to set email alerts
|

Scale sensitivity and question order in the contingent valuation method

Abstract: This study examines the effect on respondents' willingness to pay to reduce mortality risk by the order of the question in a stated preference study. Using answers from an experiment conducted on a Swedish sample where respondents' cognitive ability was measured and where they participate in a contingent valuation survey it is found that scale sensitivity is the strongest when respondents are asked about a smaller risk reduction first ("Bottom-up" approach). This contradicts some previous evidence in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…We focused on range effects and WTP versus WTA. Andersson and Svensson point to additional features that may become important, notably the size of the assessed risk change [ 40 ]. If the risk change is not determined by substantial factors of the policy question at hand, it may be useful to also consider that dimension.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on range effects and WTP versus WTA. Andersson and Svensson point to additional features that may become important, notably the size of the assessed risk change [ 40 ]. If the risk change is not determined by substantial factors of the policy question at hand, it may be useful to also consider that dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also found that individuals anchor reported probabilities based simply on the order in which questions appear, such that the characteristics of the initial question affect reported values on subsequent questions (Andersson and Svensson, ; O'Hagan et al., ; Wright and Anderson, ). Question order effects have been observed in a wide range of subjective valuation and expectation studies, including the willingness to pay for health‐care programs (Stewart et al., ) and perceived risk of developing cancer (Taylor et al., ).…”
Section: Sanction Risk Perceptions and Deterrencementioning
confidence: 99%
“…the public element of the common‐pool resource is dominated by the private element, where sensitivity to scope still applies in a significant degree due to the increased (private) benefit that the farmer obtains. This interpretation could also apply to Andersson and Svensson's () results, which also show order effects but still some differences in the degree of sensitivity to scope in the valuation of decreased mortality risk from bus accidents. They refer to it as a non‐pure private good in which values might contain an element of paternalistic altruism, but that is likely to be less strong than the private benefit of reducing one's own personal risk of dying in a bus accident.…”
Section: Discussionmentioning
confidence: 84%
“…Results from the Probit model (Table ) indicate that age, education level, tree density and farm income influence the likelihood of being sensitive to scope. Regarding age, Nielsen and Kjær () and Andersson and Svensson () also found that younger respondents are more likely to be sensitive to scope. The education level was also significant in Nielsen and Kjær (), but contrary to our results, they found that higher levels of education positively affect the likelihood of sensitivity to scope.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation